Standardizing the Response to Category II Tracings during Induction with Oxytocin: A Cost-Effectiveness Analysis - Chatroux, Louisa R.; Savitsky, Leah M.; Zwerling, Blake; Williams, Justin; Cahill, Alison G.; Caughey, Aaron B. (American Journal of Perinatology, 2017)
Background Oxytocin is one of the most frequently used medications in obstetrics. It is generally considered to be safe and effective for induction and augmentation of labor but has been implicated in uterine hyperstimulation and adverse fetal outcomes. The management of labor with oxytocin in response to changes in fetal status remains an area of debate.Objective This study sought to assess the cost-effectiveness of reducing or ceasing oxytocin administration in response to Category II fetal heart rate tracings.Study Design A decision-analytic model was built using TreeAge 2016 software (TreeAge Software Inc.) with probabilities, costs, and utilities derived from the literature. Primary outcomes included cerebral palsy (CP), neonatal mortality, and mode of delivery. Secondary outcomes included cost per quality-adjusted life year (QALY; cost-effectiveness threshold set at $100,000/QALY), admission to the neonatal intensive care unit (NICU), and low 5-minute Apgar score (<7). Sensitivity analyses were performed to determine the robustness of our baseline assumptions.Results In a theoretical cohort of 900,000 women (estimated number of women undergoing induction at term in the United States), decreasing or stopping oxytocin in response to Category II tracings prevented 12,510 NICU admissions, 4,410 low Apgar scores, 204 neonatal deaths, and 126 cases of CP. However, there were 81,900 more cesarean deliveries. The strategy cost $356 million more, but was cost-effective with an ICER of $9,881.5 per QALY. Sensitivity analysis revealed that the intervention would be cost-effective up to a cesarean rate of 54%.Conclusion Decreasing or stopping oxytocin in response to Category II fetal heart rate tracings is cost-effective. This intervention increases the rate of cesarean deliveries but reduces neonatal morbidity and mortality. Further work on this guideline should be performed to ascertain how the approach using different aspects of the Category II tracing to guide care might lead to similar improved outcomes without increasing the cesarean delivery rate.
Keywords: Category II tracing; cost-effectiveness; fetal heart rate monitoring; induction; labor management; oxytocin